Centralisation of corporate governance framework for Islamic financial institutions: is it a worthy cause? - Abd Hakim Abd Razak (ISRA International Journal of Islamic Finance, 2018)
Purpose: The purpose of this paper is to supply basic insights into the principle of shūrā (consultation) in Islamic banking, the idea of a centralised approach to the corporate governance of Islamic financial institutions (IFIs), the roles of a centralised Sharīʿah board as the highest authority on Sharīʿah issues and its distinguishing features from a de-centralised system and the advantages and disadvantages of the two governance systems. Design/methodology/approach: In analyzing these, the paper adopts the critical legal studies approach and refers to the provisions of the Qurʾan and Sunnah, ijmāʿ (consensus) of Sharīʿah scholars and recent Islamic banking reports.: Findings: Despite the fact that the double-digit growth of the current US 2tn Islamic banking industry is a promising sign for its further expansion - expecting to cross the US6.5tn mark by 2020 - there remains concern over the lack of standardization or rather the diversified approaches to the corporate governance of IFIs across key Islamic banking regions.Practical implications There has been much debate surrounding the issue of whether the Islamic banking industry requires a centralised Sharīʿah board at the state level to complement the Sharīʿah boards at the IFIs' individual level in providing better supervision of the Sharīʿah-compliance of IFIs. The fact that the industry is already equipped with two prominent standard-setting agencies in the form of the AAOIFI, the IFSB does little to suggest that best governance practices - which centre around the themes of consistency, harmony and uniformity - are on the horizon, at least not whilst their issued standards and guidelines remain voluntary for IFIs. Originality/value All in all, it is aspired that this paper may assist the reader in evaluating the pros and cons of the whole concept of Sharīʿah board centralisation.
Keywords: 330; Central Sharīʿah board; Centralisation; Corporate governance; Ikhtilāf al-fuqahāʾ; Shūrā